Sustained and continuously improved efficacy of tildrakizumab in patients with moderate-to-severe plaque psoriasis. (16th November 2020) - Elewski, Boni; Menter, Alan; Crowley, Jeffrey; Tyring, Stephen; Zhao, Yang; Lowry, Simon; Rozzo, Stephen; Mendelsohn, Alan M.; Parno, Jeffrey; Gordon, Kenneth
Abstract: Background: Tildrakizumab is a high-affinity, humanized, IgG1 κ, anti-interleukin-23 monoclonal antibody approved for moderate-to-severe plaque psoriasis. Objectives: This analysis examined whether tildrakizumab's week-28 efficacy can be sustained or improved to week 52. Methods: Psoriasis patients on the same-dose tildrakizumab (100 or 200 mg) in the first 52 weeks achieving week-28 PASI ≥50 were pooled from two phase-3 randomized controlled trials, and grouped into four mutually exclusive week-28 PASI response groups. Patients' week-52 PASI responses were compared to their week-28 PASI responses. Results: Of 352 patients receiving 100-mg tildrakizumab, 10.5%, 25.3%, 38.4%, and 25.9% achieved PASI 50–74, 75–89, 90–99, and 100 at week 28, respectively. Among patients achieving PASI ≥90, ≥75, or ≥50 at week 28, 89.4%, 91.1%, or 97.4% maintained their week-28 PASI responses at week 52, respectively. Among patients achieving PASI 50–74, 75–89, or 90–99 at week 28, 64.8%, 33.7%, or 25.2% improved their week-28 PASI responses at week 52, respectively. Limitations: This post hoc analysis may be less robust than an a priori analysis. Conclusions: Most tildrakizumab-treated patients with week-28 PASI ≥75 maintained their week-28 PASI improvement at week 52. More than half of week-28 partial responders (PASI 50–74) improved their PASI responses to PASI ≥75 at week 52. Clinicaltrials.gov identifiers: NCT01722331, NCT01729754.